Contribution of Indonesian Sharia Banking to Sustainable Economic Development Until 2023 - Sakifah, Sakifah; Masitoh, Noneng (AIBPM Publisher, 2023)
Sharia banking as one of the pillars of the country's economy has an important role in realizing sustainable economic development. This article aims to present empirical facts about the contribution of Indonesian sharia banking in realizing a sustainable economy through data collected from various sources, academic references and facts in the field obtained from direct observation. News records published by trusted institutions, company activity reports and financial reports are considered important sources in this research. The method used in preparing this article is descriptive qualitative with secondary and primary data from various relevant sources. The research results show that the important role of sharia banking in Indonesia is not only contained in government regulations, the central bank, the financial services authority, agreements and policy directions on paper but has become a real action in the context of realizing a developed Indonesia in 2045. Improvement and development of programs It is also discussed so that it can become a reference for achieving sustainable economic goals in harmony with current digital technology.